Transformation of Human Resources Risk Management in Higher Education: An Adaptive Approach Towards Changes in Education Policy - Putro, Suryati Eko; Bernadetha Nadeak; Yeyen Subandi; Hady Sofyan (International Journal of Economics (IJEC), 2025)
The transformation of Human Resources (HR) risk management in higher education is becoming increasingly crucial in facing the dynamics of changes in education policy in Indonesia. This study aims to analyze how higher education institutions implement an adaptive approach in managing HR risk in order to improve organizational effectiveness and institutional competitiveness. The research method used is qualitative with a case study approach and comparative analysis of several higher education institutions in Indonesia. The results of the study indicate that the success of HR risk management is highly dependent on policy flexibility, investment in improving the competence of educators, the implementation of a transparent evaluation system, and attention to the welfare of educators. Higher education institutions that implement an adaptive HR risk management model are proven to be better prepared in facing policy changes and are able to develop into more competitive educational institutions. Therefore, this study recommends the formulation of more flexible and data-based policies to improve the resilience and innovation of higher education institutions in Indonesia.